Selection and Performance of Antifungal Lactic Acid Bacteria in Corn Mini-Silos - Carrizo, Natalí Ivana (2022)
Silage is a method of forage conservation based on lactic fermentation. In order to improve the fermentative performance in corn silages, the aims of the present work were as follows: (I) to screen lactic acid bacteria with acidifying activity, (II) to study their antifungal activity against filamentous fungi and yeasts and (III) to evaluate their performance as antifungal in mini-silos. The acidifying activity was determined by measuring the pH and total titratable acidity. Those most acidifying bacteria were incubated in plates together with fungal markers strains to observe the presence or absence of inhibition halos, in addition to studying the nature of the antifungal metabolites by means of the treatment with proteases. The strain with the widest spectrum of action was selected to formulate an inoculum used in corn mini-silos. During storage, both silos determined humidity, acidification and microbiological composition, and then aerobic stability. The results showed that Lactoplantibacillus (L.) plantarum cultures had a higher production of lactic acid (7.7–17.5 g/L) than Pediococcus (8.8–10.9 g/L). L. plantarum CRL363 could inhibit the growth of filamentous fungi and some yeasts and consequently it was used in mini-silos. Compared to the control, the inoculated silo presented low pH values (4.02–4.85) and low fungi and yeast count until 20 days of storage, demonstrating the great potential of CRL363 strain for the formulation of inoculants for corn silage.